Experimental and numerical investigation of comparability of whiplash sled test results - ÖZDEMİR, MUSTAFA (SPRINGER HEIDELBERG, 2016)
Whiplash-associated neck injuries represent an important health and socioeconomic problem attracting more and more attention of the vehicle safety community. Sled tests are conducted for the dynamic whiplash assessment of seats. However, reproducibility of the initial backset distances and of the sled pulses in every test plays an important role on the comparability of these results. In this study, in order to investigate these aspects, three different driver seat types are considered with three identical and unused samples for each of them, and by strictly following the European New Car Assessment Program (Euro NCAP) whiplash protocol and using the BioRID II dummy, totally nine sled tests are performed. The sled pulses are in general reproduced quite well for different vehicle seats in these tests. However, it is seen that there are differences of up to 5 mm in the initial backset distances recorded for the identical seats of the same type, while this difference increases up to 7 mm among the different seat types considered. Moreover, taking into account the associated tolerances allowed in this protocol, this uncertainty in the backset can even increase up to 10 mm. Based on the previous simulation results obtained by using the finite element model of the BioRID II dummy, linear regression models are constructed, and it is shown that a 10-mm increase in the backset will yield an increase of 2.25, 2.89 and 3.11 m(2)/s(2) in the NICmax values for the low, medium and high severity Euro NCAP pulses, respectively. Being 38, 22 and 31 % of the differences between the associated Euro NCAP higher and lower performance limits, and 68, 96 and 124 % of the differences between the associated Euro NCAP lower performance and capping limits, such increases in the NICmax values are found to bring an unacceptably high uncertainty in the test results, and they can even easily lead to the application of capping, which means giving a zero score for the entire test. In light of these findings, several suggestions are recommended for a more solid whiplash dynamic assessment procedure.
Keywords: Whiplash; Neck injury; Rear crash; Vehicle seat; Vehicle safety; INJURY; KINEMATICS